Velikonočna misel liberalne strani od razcepa v slovenski politiki 1890 do konca avstrijske dobe 1918 - Perovšek, Jurij (Acta ecclesiastica Sloveniae, 2024)
Despite the attacks on the Catholic church, clergy, and Catholic faith, liberal Slovenians were, from the dogmatically sacramental aspect, loyal Catholics in private life. What differed was their understanding of certain dimensions of Christianity, more precisely of Catholicism, as a religion. Regarding the role of the Catholic faith and the Church in one’s public or social life, they rejected the political dimension of its religious belief. However, they unambiguously ex pressed their religious feeling upon the biggest Christian holiday – Easter. In the time of the political division in the Slovenian national movement into political Catholicism and liberalism in 1890 and until the end of the Aus trian period in 1918, the liberals put much emphasis on the annual celebration of Easter. Like the Catholic side, they frequently connected its celebration with the salutation to the arrival of spring, while at the same time highlighting »the resurrection of the greatest and most noble being that ever walked this earth«. They drew attention to Christ’s life, teaching, and suffering, the majesty of his personality, and Christ’s global historical significance. On the day of the Lord’s resurrection, they envisioned the day of victory of those ideas which are the most solid guarantee of the earthly happiness of nations and all of humanity. The liberal press also reported on Holy Week activities and Easter processions, while wishing their readers, friends, and also opponents a happy Easter. The liberals (and the Catholics and social democrats) also connected the celebration of Easter with the desire for national uprising – Slovenian national, political, economic, cultural, and social emancipation. They also saw an opportunity to express their general idealistically political views. They reproached the Catholic side for exploiting the faith for political purposes, striving for temporal power through the operation of the Catholic church and clergy, and directing social thought according to their ideological and political views. While following the religious and existential meaning of Easter they persisted in the ongoing cultural struggle. Prior to the end of the Austrian period in 1918, the newspaper Slovenski narod published an illustrative Easter message discussing the great destiny awaiting Slovenians and the opening of the doors to a new life, a better and greater one than our grandfathers and fathers dared to dream of. The Slovenski narod then emphasised the principle of self-determination as the only redemptive path towards national freedom.
Keywords: Austrian period; avstrijska doba; cultural struggle; Easter; kulturni boj; liberalci; liberals; majesty of Christ's personality; narodno vstajenje; national resurrection; veličastnost Kristusove osebnosti; velika noč